Creative-scientific decision-making skills learning model for training creative thinking skills and student decision making skills - Siagian, Asister Fernando; Ibrahim, Muslimin; Supardi, Zainul Arifin Imam (Nurture, 2023)
Purpose: This study aims to produce a valid learning model by validating the creative-scientific decision -making skills (CSDMS) learning model to improve creative thinking skills and decision-making skills. Design/Methodology/Approach: The research methodology is development research adapted from Borg and Gall which consists of three stages: the preliminary stage, the model design stage and the model testing stage. This research is conducted through validation study designs those tests two criteria, namely content and construct validity by involving three experts in Focus Group Discussion (FGD) activities. The validity criteria were determined based on the Aiken validation index. Findings: The study’s findings show that the CSDMS model is valid in terms of content and construct. This is based on calculations using the Aiken formula which shows that the V value for each instrument item is 0.89 ≤ V ≤ 1 with a very valid category. It was concluded that the CSDMS model was stated to be valid both in terms of content and construct validity in order to improve students’ creative thinking skills and decision-making skills. Contribution to literature: This research produces a valid learning model in terms of content and construct, so that it can improve creative thinking skills and decision-making skills. The CSDMS model has a syntax consisting of six phases, namely: 1) Problem orientation 2) Exploration 3) Elaboration 4) Group investigation 5) Decision making and 6) Evaluation and reflection.